2017
DOI: 10.18203/2394-6040.ijcmph20171324
|View full text |Cite
|
Sign up to set email alerts
|

Food taboos among pregnant and lactating mothers in Tumkur: a qualitative study

Abstract: Background: Maternal nutrition has a huge impact on the health of the mother and the fetus. Pregnancy imposes the need for considerable extra calorie and nutrient requirements. A food taboo is a prohibition against consuming certain foods. The restrictions imposed on people forces them to abstain from certain food and drinking items as these things are embedded into the cultural and religious threads. Methods: A qualitative study was conducted between July 2014 and September 2014. Study was conducted in urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…15 Chakrabarti et al reported that taboos were present regarding consumption of various fruits (banana, papaya, jackfruit, coconut), vegetables (brinjal, leafy vegetables), meat, fish, and eggs during pregnancy. 16 These were followed mainly to prevent miscarriage, promote easy delivery, and prevent foetal malformations. Shwetha et al reported that, during pregnancy, some of the foods were specifically restricted during the first and second trimester, while certain others were forbidden throughout gestation.…”
Section: Figure 1: Inclusion and Avoidance Of Special Food Items Duri...mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Chakrabarti et al reported that taboos were present regarding consumption of various fruits (banana, papaya, jackfruit, coconut), vegetables (brinjal, leafy vegetables), meat, fish, and eggs during pregnancy. 16 These were followed mainly to prevent miscarriage, promote easy delivery, and prevent foetal malformations. Shwetha et al reported that, during pregnancy, some of the foods were specifically restricted during the first and second trimester, while certain others were forbidden throughout gestation.…”
Section: Figure 1: Inclusion and Avoidance Of Special Food Items Duri...mentioning
confidence: 99%
“…19 In a study conducted by Chakrabarti et al reported that taboos in the lactation included avoidance of small fish, foods with multiple seeds, other "cold" foods, and fluid restriction in some areas. 16 The taboos were followed spontaneously as the inhibitions were imposed only for a definite period. A study by Bista found that, most of the participants expressed that they avoided black pulses (Kalodaal) and pulses as they believed that taking vegetables, daal or pulses after delivery can cause digestive problems to the baby like flatulence and pain in the abdomen.…”
Section: Figure 1: Inclusion and Avoidance Of Special Food Items Duri...mentioning
confidence: 99%